Dance and the Hollywood Latina : Race, Sex, and Stardom - Ovalle, Priscilla Peña (Book collections on Project MUSE., 2010)
Dance and the Hollywood Latina asks why every Latina star in Hollywood history began as a dancer or danced onscreen. Introducing the concepts of "inbetween-ness" and "racial mobility" to further illuminate how racialized sexuality and the dancing female body operate in film, this book focuses on the careers of Dolores Del Rio, Rita Hayworth, Carmen Miranda, Rita Moreno, and Jennifer Lopez and helps readers better understand how the United States grapples with race, gender, and sexuality through dancing bodies on screen.